Association between Physical Inactivity and Academic Record in Korean Adolescents - Wi-Young So; Yi-Soo Shin (Tehran University of Medical Sciences, 2012)
Background: The purpose of this study was to investigate the association between physical inactivity and academic record in Korean adolescents.Methods: Adolescent students from the first grade of middle school to the third grade of high school (n=75,066)participated in the 5th Korea Youth Risk Behavior Web-based Survey project in 2009. The association between physical inactivity and academic record was assessed using multivariate logistic regression analysis after adjusting for gender, age, body mass index, family's socioeconomic status, parents' education level, and frequency of vigorous ormoderate physical activity (PA) as well as muscular strength exercises.Results: During weekdays, the odds ratios (ORs) (95% confidence interval [CI]) for reporting a higher than average academic record, as compared with <1 hour of physical inactivity per day, was 0.796 (0.761-0.832, for ≥1 to <2hours, 0.632 (0.603-0.663, for ≥2 to <3 hours, 0.567 (0.535-0.601, for ≥3 to <4 hours, and 0.494 (0.468-0.522, P <0.001 for all cases) for ≥4 hours of physical inactivity per day. During the weekends, the ORs (95% CI) for reporting ahigher than average academic record, as compared with <1 hour of physical inactivity per day, were 0.901 (0.848-0.957, P = 0.001) for ≥3 to <4 hours and 0.785 (0.743-0.830, P < 0.001) for ≥4 hours of physical inactivity per day.Conclusion: Korean adolescents who spend more time engaged in physical inactivity are predisposed to a belowaverageacademic record.